PENGARUH CURRENT RATIO (CR) DAN TOTAL ASSET TURNOVER (TATO) TERHADAP RETURN ON ASSET (ROA) PADA PT. BERLINA TBK PERIODE TAHUN 2013-2023 - Berka Endy Kusuma; Asep Muhammad Lutfi (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of the Current Ratio and Total Assets Turnover either partially or simultaneously on the Return on Assets at PT. Berlina Tbk. The approach used in this research is the Balance Sheet and income statement of PT. Berlina Tbk period 2013-2023. The independent variables used in this study consisted of the Current Ratio and Total Assets Turnover, while the dependent variable was Return on Assets. The data collection technique used in this study used a documentation study. The data analysis technique uses multiple linear regression analysis, classical assumption test, t test, F test and coefficient of determination, with SPSS 26 software. The results of this study prove that the Current Ratio partially has no effect on Return On Assets. The result of tcount2,116< ttablel2,306, where the sig value is 0,067>0,05. while Total Assets Turnover has an influence on Return on Assets. The result of tcount2,527>ttablel2,306, where the sig value is 0,035<0,05. And simultaneously Current Ratio and Total Assets Turnover have an influence on Return on Assets at PT. Berlina Tbk. It is proven from the F test result that the Fcount 7,996> Ftable4,46 and the sig value is 0,012< 0,05.